Collaborative, Reflective, and Iterative Japanese Lesson Study in an Initial Teacher Education Program: Benefits and Challenges - Chassels, Caroline; Melville, Wayne (Canadian Journal of Education/Revue canadienne de l’éducation, 2010)
To investigate benefits and challenges to engage teacher candidates in Japanese lesson study, defined as a collaborative, reflective, and iterative teacher development pro‐ cess, we analyzed reflective papers submitted by 60 teacher candidates studying at an Ontario faculty of education, engaged 20 practicum associate teachers in a group dis‐ cussion, and considered the reflective notes of the course instructor (first author). Findings suggest that Japanese lesson study provides opportunities for teacher candi‐ dates to build professional learning communities, to deepen understanding of curric‐ ulum and pedagogy, and to develop habits of critical observation, analysis, and ref‐ lection. Although benefits of lesson study are numerous and significant, our research identified implementation challenges related to time, practicum placements, and the professional development of associate teachers. Key Words: professional learning communities, reflective practice, teacher collabora‐ tion En vue d’analyser les avantages et les défis reliés à l’étude de leçon japonaise, une méthode de formation à l’enseignement axée sur la collaboration, la réflexion et l’itération, les auteurs ont (1) analysé les réflexions écrites de 60 candidats à l’enseignement étudiant dans une Faculté d’éducation en Ontario, (2) réuni 20 ensei‐ gnants associés pour une discussion en groupe et (3) analysé les notes de l’instructeur du cours. Les observations ainsi colligées donnent à penser que l’étude de leçons japonaises permet aux futurs enseignants de créer des communautés d’apprentissage professionnelles, de mieux comprendre le curriculum et la pédagogie et de dévelop‐ per des habitudes d’observation, d’analyse et de réflexion critiques. Bien que les avantages de l’étude de leçon soient nombreux et importants, cette recherche met en lumière les difficultés que pose sa mise en œuvre, notamment le temps requis, les endroits à trouver pour les stages et le perfectionnement professionnel des ensei‐ gnants associés. Mots clés : communautés d’apprentissage professionnelles, pratique réflexive, colla‐ boration du personnel enseignant.